Effects of water deficit on the growth and yield formation of maize (Zea mays L.) - Salifu, Mahama (Acta Agraria Debreceniensis, 2017)
Maize (Zea mays L.) is the most important consuming cereal crop in the world after rice and wheat. This requires an understanding of various management practices as well as conditions that affect maize crop performance. Water deficit stress during crop production is one of the most serious threats to crop production in most parts of the world and drought stress or water deficit is an inevitable and recurring feature of global agriculture and it is against this background that field study of crops response to water deficit is very important to crop producer and researchers to maximize yield and improve crop production in this era of unpredicted climatic changes the world over. A pot experiment was carried out to determine the effects of water deficit on growth and yield formation of maize. Two maize cultivars were used Xundan20 and Zhongdan5485. Three levels of soil water content were used in two stages of water control levels at two stages of the maize plant development 1. The JOINTING STAGE: A. CONTROL (CK) soil water content: from 70% to 80% of soil water holding capacity at the field, soil water content: from 55% to 65% of soil water holding capacity at the field, soil water content: from 40% to 50% of the Soil water holding capacity at the field. 2. The BIG FLARE PERIOD: A. CONTROL (CK) soil water content: from 75% to 85% of soil water holding capacity at the field, soil water content: from 58% to 68% of soil water holding capacity at the field, soil water content: from 45% to 55% of the soil water holding capacity at the field. This research mainly studied the effects of water deficit on physiological, morphology and the agronomical characteristics of the maize plant at the different water stress levels. The importance of these results in this experiment will enable plant producers to focus and have a fair idea as to which stage of the maize plant’s development that much attention must be given to in terms of water supply.